Trichoderma gamsii (NFCCI 2177): A newly isolated endophytic, psychrotolerant, plant growth promoting, and antagonistic fungal strain. (8th April 2013) - Rinu, K.; Sati, Priyanka; Pandey, Anita
Abstract An endophytic fungus has been isolated from the lateral roots of lentil (Lens esculenta Moench), growing under mountain ecosystem of Indian Himalayan Region (IHR). While the fungus was observed as fast growing with white scanty mycelium turning to turmeric brown in 5 days of incubation at 25 °C, it also produced a unique odor. The fungus exhibited growth between 4 and 30 °C (optimum 25 °C) and tolerated pH between 2.0 and 13.5 (optimum 4–6). Based on phenotypic (colony morphology and microscopy) and genotypic (18S rRNA analysis) characters, the fungus was identified as Trichoderma gamsii (99% similarity). The fungus was evaluated for its plant growth promotion and biocontrol properties. The fungus was found to be positive for phosphate solubilization, chitinase activity, and production of ammonia and salicylic acid, while the results for production of IAA, HCN, and siderophores were negative. Out of the seven phytopathogenic fungi tested, it showed antagonism against six. Bioassays conducted under green house using four test crops (two cereals and two legumes) showed its potential in plant growth promotion. The fungus has potential to be developed as a bioformulation for application under mountain ecosystem.